2011
DOI: 10.1037/a0025077
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and intimate partner violence perpetration among college students: Assessing the temporal association using electronic diary technology.

Abstract: Objectives: The primary goals of this study were to assess the temporal relationship between alcohol use and intimate partner violence (IPV) perpetration using state-of-the-art electronic diary assessment methods and to examine the extent to which distal factors (e.g., sex, psychopathology, relationship satisfaction) moderated that association. Method: Participants were 184 male and female college students in dating relationships who used a handheld computer to answer daily questions about alcohol use and IPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
137
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(163 citation statements)
references
References 38 publications
20
137
6
Order By: Relevance
“…In the one known study that compared the effects of alcohol on dating violence perpetration among men and women, men were more likely to perpetrate psychological aggression on a drinking day compared with women (Moore et al, 2011). However, men and women did not differ in their likelihood to perpetrate physical aggression on drinking days.…”
Section: Alcohol and Dating Violencementioning
confidence: 93%
See 3 more Smart Citations
“…In the one known study that compared the effects of alcohol on dating violence perpetration among men and women, men were more likely to perpetrate psychological aggression on a drinking day compared with women (Moore et al, 2011). However, men and women did not differ in their likelihood to perpetrate physical aggression on drinking days.…”
Section: Alcohol and Dating Violencementioning
confidence: 93%
“…In one of the fi rst known studies to examine the daily association between alcohol use and dating violence among male and female youth ages 17-21, Rothman et al (2012b) found that, compared with nondrinking days, dating violence perpetration was more likely on drinking days and heavy drinking days. Similarly, in a sample of college men and women, psychological and physical dating violence perpetration were more likely on drinking days compared with nondrinking days and as the number of drinks consumed increased (Moore et al, 2011).…”
Section: Alcohol and Dating Violencementioning
confidence: 99%
See 2 more Smart Citations
“…Alcohol intoxication may serve this function by impairing inhibitory control and rendering an individual less able to override aggressive urges when instigated. A large literature linking alcohol consumption to IPA supports the role of drinking as a disinhibiting factor (Eckhardt, 2007;Moore, Elkins, McNulty, Kivisto, & Handsel, 2011;Rapoza & Baker, 2008). However, as with other risk factors, alcohol consumption does not invariably lead to behavioral disinhibition, but is most potent in predicting IPA in the presence of other risk factors (e.g., Schumacher, Coffey, Leonard, O'Jile, & Landy, 2013).…”
mentioning
confidence: 99%